Determination of Ibuprpfen in Aqueaus Solutions and Pharmacetical Preparations by UV-VIS Spectrophotometric. - Jasim, Hadi H; Abed, Nehad K (Al-Nahrain Journal of Science, 2015)
A method has been developed for the determination of the ibuprofen drug in aqueous solution and pharmaceutical preparation using UV-Vis spectrophotometry. The opitimum experimental condition were based on the formation of complex compound and studied, the best temperature (303 k°), reaction time (13 min), solvent extraction (3 ml) and extraction time (5 min). Mole ratio and Job –method was used to found the ratio between the ligand (drug) and the metal ion (Co), the complex output ratio of (1:1). Detection of limit =0.223 µg/ml, Re% =96.8, r =0.9561, linearity (1x10-3 – 2x10-2 M) and sandell sensitivity S =0.1008.